Pharmaceutical Experimental Design - Lewis, Gareth A.; Mathieu, Didier; Phan, Roger Tan Luu (New York Informa healthcare, 2010)
This useful reference describes the statistical planning and design of pharmaceutical experiments, covering all stages in the development process - including preformulation, formulation, process study and optimization, scale-up, and robust process and formulation development.
Keywords: Drugs - Design; Research Design